2021
DOI: 10.1155/2021/6613198
|View full text |Cite
|
Sign up to set email alerts
|

The Extended Oxidative and Sensory Stability of Traditional Dairy-Based Oil with Steam-Distilled Essential Oils Extracted from the Bioactive-Rich Leaves of Ziziphora tenuior, Ferulago angulata, and Bunium persicum

Abstract: The oxidation rate and overall sensory acceptability of Iranian animal oil (IAO) during storage were evaluated after adding the bioactive essential oils extracted from medicinal herbs of Ziziphora tenuior, Ferulago angulata, and Bunium persicum. Results showed that the most dominant chemical constituents in Z. tenuior, F. angulata, and B. persicum essential oils were pulegone (12.77%), ferulagon (14.97%), and (+)-trans-carveol (57.70%), respectively. IAO contained more saturated fatty acids (67.43%, mainly pal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Distillation procedures are also extensively used in the isolation of essential oils from their natural sources [71,72]. For this purpose, the plants or their specific part are incorporated over water into a distillation apparatus.…”
Section: Isolation Of Eosmentioning
confidence: 99%
“…Distillation procedures are also extensively used in the isolation of essential oils from their natural sources [71,72]. For this purpose, the plants or their specific part are incorporated over water into a distillation apparatus.…”
Section: Isolation Of Eosmentioning
confidence: 99%
“…Mohammadi reported that the main chemical constituents in Z. tenuior, F. angulata, and B. persicum essential oils were pulegone (12.77%), ferulagon (14.97%), and (+)-trans-carveol (57.70%), respectively. However, higher total phenolic content, total flavonoid content, total carotenoid, and total chlorophyll in B. persicum essential oil were found compared to Z. tenuior and F. angulata essential oils (Mohammadi et al, 2021).…”
Section: Sensory Evaluation Of Iao Treatmentsmentioning
confidence: 78%
“…The treatment containing 5% F. angulata had the highest TBA value, whereas treatments with B. persicum had the lowest increase in TBA value during storage (P < 0.05). This can be due to the increase in the latter's phenolic and limonene compounds that inhibited oxidation more effectively (Mohammadi et al, 2021). The high aromatic compound content of F. angulata, on the other hand, was not as effective in inhibiting the oxidation process.…”
Section: Av Pv Tba Values and Os Analysis Of Different Iao Treatmentsmentioning
confidence: 96%
See 1 more Smart Citation